Effects of Habitat River Microbiome on the Symbiotic Microbiota and Multi-Organ Gene Expression of Captive-Bred Chinese Giant Salamander - Zhu, Wei; Zhao, Chunlin; Feng, Jianyi; Chang, Jiang; Zhu, Wenbo; Chang, Liming; Liu, Jiongyu; Xie, Feng; Li, Cheng; Jiang, Jianping; Zhao, Tian (Frontiers in Microbiology, 2022)
Reintroduction of captive-bred individuals is a primary approach to rebuild the wild populations of Chinese giant salamander (Andrias davidianus), the largest extant amphibian species. However, the complexity of the wild habitat (e.g., diverse microorganisms and potential pathogens) potentially threatens the survival of reintroduced individuals. Here, fresh (i.e., containing environmental microbiota) or sterilized river sediments (120 ℃ sterilized treatment) were added to the artificial habitats to treat the larvae of Chinese giant salamander (control group – Cnt: 20 individuals, treatment group 1 with fresh river sediments – T1: 20 individuals, and treatment group 2 with sterilized river sediments – T2: 20 individuals). The main objective is to test whether this procedure could provoke their wild adaptability from the perspective of commensal microbiotas (skin, oral cavity, stomach, and gut) and larvae transcriptomes (skin, spleen, liver, and brain). Our results indicated that the presence of habitat sediments (whether fresh or sterilized) reshaped the oral bacterial community composition. Specifically, Firmicutes decreased dramatically from ~70% to ~20–25% (mainly contributed by Lactobacillaceae), while Proteobacteria increased from ~6% to ~31–36% (mainly contributed by Gammaproteobacteria). Consequently, the proportion of antifungal OTUs increased, and the function of oral microbiota likely shifted from growth-promoting to pathogen defense. Interestingly, the skin microbiota, rather than the colonization of habitat microbiota, was a major source of the pretreated oral microbiota. From the host perspective, the transcriptomes of all the four organs were changed for treated individuals. Specifically, the proteolysis and apoptosis in the skin were promoted, and the transcription of immune genes were activated in the skin, spleen, and liver. Importantly, more robust immune activation was detected in individuals treated by sterilized sediments. These results suggested that the pathogen defense of captive-bred individuals was improved after being treated, which may benefit their survival in the wild. Taken together, our results suggested that the pre-exposure of captive-bred Chinese giant salamander individuals to habitat sediments could be considered and added into the reintroduction processes to help them better adapt to wild conditions.